2011
DOI: 10.1007/s13197-011-0399-8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling moisture diffusivity, activation energy and specific energy consumption of squash seeds in a semi fluidized and fluidized bed drying

Abstract: This study investigated thin layer drying of squash seeds under semi fluidized and fluidized bed conditions with initial moisture content about 83. 99% (d.b.). An experimental fluidized bed dryer was also used in this study. Air temperature levels of 50, 60, 70 and 80°C were applied in drying samples. To estimate the drying kinetic of squash seed, seven mathematical models were used to fit the experimental data of thin layer drying. Among the applied models, Two-term model has the best performance to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 27 publications
7
42
0
Order By: Relevance
“…Thus, the Midilli et al and Two Term models were found to be best models to represent the thin-layer drying characteristics of the date slices. These observations are in good agreement with earlier results reported for the Midilli et al model in describing the thin-layer drying of pear (Doymaz, 2013) and mango ginger (Murthy & Manohar, 2014) and for the Two term model in drying of sultana grapes (Yaldiz et al, 2001) and squash seeds (Chayjan et al, 2013).…”
Section: Fitting Of Drying Curvessupporting
confidence: 92%
“…Thus, the Midilli et al and Two Term models were found to be best models to represent the thin-layer drying characteristics of the date slices. These observations are in good agreement with earlier results reported for the Midilli et al model in describing the thin-layer drying of pear (Doymaz, 2013) and mango ginger (Murthy & Manohar, 2014) and for the Two term model in drying of sultana grapes (Yaldiz et al, 2001) and squash seeds (Chayjan et al, 2013).…”
Section: Fitting Of Drying Curvessupporting
confidence: 92%
“…(4) could be written as the first term of series only, without much effect on the prediction accuracy (Odjo et al 2012;Amiri Chayjan et al 2013):…”
Section: Methodsmentioning
confidence: 99%
“…Fluidization is defined as suspending the vegetable bed (dill leaves, Anethum sowa L.) in air flow. With gradually increasing airflow through a bed of vegetable, fixed bed, minimum fluidized bed (semifluidized bed), bubbling fluidized bed and transportation will be created, respectively (Chayjan et al, 2011).Several authors had attempted to determine mathematical models for estimation of the moisture ratio and drying rate of food and biological materials during the drying process in eg potato (Bakal et al, 2011), Cuminum cyminum (Zomorodian and Moradi, 2010), carrot (Doymaz, 2004, sweet cherry (Doymaz and Ismail, 2011), and berberies (Gorjian et al, 2011). Some researchers have studied the effective moisture diffusion and energy of activation in a thin layer drying of different agricultural products such as squash seeds (Chayjan et al, 2011), onion slices (Pathare and Sharma, 2006), or milky mushroom (Arumuganathan et al, 2009).…”
mentioning
confidence: 99%
“…With gradually increasing airflow through a bed of vegetable, fixed bed, minimum fluidized bed (semifluidized bed), bubbling fluidized bed and transportation will be created, respectively (Chayjan et al, 2011).…”
mentioning
confidence: 99%